Pengaruh Pengendalian Internal dan Moralitas Individu terhadap Pencegahan Kecurangan (Fraud) Akuntansi pada Perusahaan Dagang di Kecamatan Padang Barat - Dewi Zulvia; Mareli Zai (ARZUSIN, 2026)
Accounting fraud is a serious problem for trading companies because it can cause financial losses and undermine stakeholders’ trust, thereby necessitating effective internal control and high individual morality to minimize such practices. This study aimed to analyze the effect of internal control and individual morality on the prevention of accounting fraud in trading companies, with a specific focus on CV Mekkah Granit in Padang Barat Subdistrict. The research employed a quantitative approach using primary data obtained through questionnaires completed by 50 employee respondents. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that internal control and individual morality simultaneously have a significant effect on the prevention of accounting fraud. Partially, both variables also have a positive and significant effect on fraud prevention, confirming that an adequate internal control system and high individual morality play an important role in reducing fraudulent practices in trading companies. The study concludes that strengthening internal control and fostering individual morality contribute to the prevention of accounting fraud, while also supporting improved operational effectiveness and the integrity of the company’s financial statements.